SUPLEMENTASI TEPUNG UBI JALAR (Ipomoea batatas) TERHADAP KINERJA PERTUMBUHAN DAN PEMANFAATAN PAKAN IKAN LELE SANGKURIANG (Clarias gariepinus) - Fadela, Muhammad Novandy; Agustina, Agustina; Pagoray, Henny (JARI : Jurnal Akuakultur Rawa Indonesia, 2024)
This study aims to analyze the supplementation of sweet potato flour (Ipomoea batatas) with different doses in feed on growth performance and feed utilization of sangkuriang catfish (Clarias gariepinus). Sangkuriang catfish fry weighing 1.78 ± 0.11 g and length 5.90 ± 0.15 cm were reared in a container with a volume of 30 L of water and a density of 10 fish/container for 25 days. Fish were fed treated feed with doses of 0 % (P0), 1 % (P1), 2 % (P2) and 3 % sweet potato flour/kg feed (P3) three times a day at satiation. The results showed that supplementation of sweet potato flour at a dose of 1-3%/kg of feed had a better effect on growth performance and utilization of sangkuriang catfish feed than the control. Treatment with a dose of 3% sweet potato flour/kg feed (P3) showed the highest growth in weight, specific growth rate compared to other treatments, namely 5.24 g and 5.33%/day respectively. The same is shown in feed efficiency and feed conversion ratio of 69.23% and 1.44, respectively. Based on these results, sweet potato flour at a dose of 1-3 %/kg of feed can be used as a feed supplement in sangkuriang catfish farming.